2001
DOI: 10.1007/s004670100584
|View full text |Cite
|
Sign up to set email alerts
|

Reversible nephrotoxicity after overdose of colloidal bismuth subcitrate

Abstract: Although toxicity due to acute and chronic use of bismuth salts is well known, nephrotoxicity after ingestion of colloidal bismuth has been reported in few cases so far. Here we report the first case of acute renal failure (ARF) due to colloidal bismuth subcitrate overdosage in childhood. A 2-year-old boy was admitted to the hospital 6 h after ingestion of 28 De-Nol tablets (colloidal bismuth subcitrate 8.4 g). On admission, physical examination was unremarkable and he showed no signs of encephalopathy. Initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 21 publications
1
19
0
1
Order By: Relevance
“…Clear- ance of bismuth from tissues via hemodialysis was inadequate, and their patient had detectable blood bismuth levels 2 or 3 months after the agent was ingested. Islek and colleagues [10] reported a 2-year-old patient with colloidal bismuth overdose who was treated with peritoneal dialysis alone. They observed that removal of bismuth via this method was also slow.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Clear- ance of bismuth from tissues via hemodialysis was inadequate, and their patient had detectable blood bismuth levels 2 or 3 months after the agent was ingested. Islek and colleagues [10] reported a 2-year-old patient with colloidal bismuth overdose who was treated with peritoneal dialysis alone. They observed that removal of bismuth via this method was also slow.…”
Section: Discussionmentioning
confidence: 98%
“…To date, acute renal failure after overdose of colloidal bismuth has been reported in five adults and two pediatric patients (Table 2) [8,9,10,11,12,13,14]. In three of these seven cases renal biopsy showed acute tubular necrosis [11,12,13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations